NDSR ISOTOPES, PETROCHEMISTRY, AND ORIGIN OF THE SIBERIAN FLOOD BASALTS, USSR - Sharma M.; Basu A.R.; Nesterenko G.V. (My University, 1991)
The Siberian Flood Basalt Province (SFBP) of Permo-Triassic age is one of the largest flood basalt provinces with an estimated area of exposure of 337,000 km2, average thickness of 1 km, and a magma volume of 337,000 km3. Forty-seven basaltic rocks from two main subprovinces, Norilsk (5–10% of area, thickness up to 3 km) and Putorana (90–95% of area, thickness of more than 2 km), were selected, on the basis of petrography and volcano-stratigraphic relation, for major-element analysis. Twentysix of these basalts, twelve from Norilsk and fourteen from Putorana, were analyzed for Nd- and Srisotopic compositions. The Norilsk and Putorana basalts show some contrasting behavior in terms of the ratios of the highly incompatible elements of Ti, P, and K as a function of their Mg∗. The Norilsk basalts are more variable, suggesting the role of fractional crystallization-assimilation in their evolution. In contrast, the Putorana basalts show remarkable uniformity in their bulk chemical compositions.There is no overall apparent correlation between the Mg∗ and the initial ϵNd for the basalts. Most of the Putorana and some Norilsk lavas show a narrow range of initial ϵNd between 0 and +2.5 at Mg∗ = 0.53, suggesting that the bulk of the SFBP was derived from a mantle-source with near-chondritic Ndisotopic signature. Our data and six previously published analyses define a hyperbolic array near the mantle correlation line in space. However, the majority (70%) of the volumetrically significant Putorana basalts fall in the ranges of 0 to +2.5 and 0.7046 to 0.7052 for the initial ϵNd and , respectively. In Nd- and Sr-isotopic space, most of the Siberian basalts also fall within the field defined by the ocean island basalts data, implying common mantle sources. It is concluded that the SFBP originated by hotspot volcanism due to the rise of a large and relatively primitive lower mantle-derived plume beneath the Siberian continent.
Keywords: Triassic; Permian; Mesozoic::Triassic; Палеозой::Пермская; Paleozoic::Permian; Мезозой::Триасовая